Social learning and integration factors that affect first-year medical students transitioning directly from high school - Nokuthula Tlalajoe-Mokhatla; Lynette J. Van der Merwe; Mpho P. Jama (Journal of Student Affairs in Africa, 2023)
Medical student's transition from high school to a new educational environment poses academic and personal challenges that could lead to withdrawal, dismissal or failure. Students who do not feel connected to the social and academic life of the educational environment are at risk of drop-out. Hence, most medical education institutions use remediation programmes to address learning gaps and increase the chances of student success. This study aimed to identify factors that affected the social learning and integration of undergraduate medical students who had failed the first year of study. The nominal group technique (NGT) was used involving 15 participants who had completed a six-month remediation programme. Results revealed the top five ranked and themed social learning and integration factors were underpreparedness, self-management, alienation, confidence and academic advice. Self-awareness and self-management were identified as complementary skills to address these factors. The study found that students could make valuable contributions to address challenges in the educational environment and enhance successful transition. In addition to other studies recommending a focus on academic integration, these results also pointed to the importance of social integration of first-year students as they transition from high school to a new educational environment at university.